The influence of xenon-therapy on tolerance of adjuvant radiotherapy in patients with single brain metastasis - M. S. Zinkovich; L. Y. Rozenko; A. I. Shikhlyarova; G. V. Gukova; Y. Y. Arapova; T. P. Protasova (Медицинский вестник Юга России, 2018)
Objective: to study the tolerance of radiotherapy by adding the boost and the xenon-therapy during the whole brain radiotherapy (WBRT) in patients with single brain metastasis. Materials and methods: the study involved 60 patients divided in the 3 equal groups (20 people in each group) where the treatment varied according the methods of the adjuvant radiotherapy. The patients in the first group were assigned to receive WBRT alone, in the second group — WBRT and the boost to tumor bed, in the third group — WBRT and the boost in combination with the xenon-oxygen inhalations. The quality of life, the toxic and adaptation reaction, the psychological status and the electrical activity of the brain during the treatment were also included in the research. Results: the increase of side-effects of the treatment and the quantity of stress-reactions occurred during WBRT in combination with the boost. But the use of xenon allowed to level all the negative reactions and even to improve some of physiological and psychological parameters. The xenon-oxygen inhalations led to the decrease of intensity of situational anxiety and depression. There was also a reduction in delta-activity level according to EEG and a return of the other rhythms to baseline levels which was lacking in the other groups. Conclusions: the use of the xenon-therapy in combination with WBRT by the developed methods allows to improve the quality of life in patients with radiation treatment, as well as to reduce the degree of the intensity of side and toxic reactions. The results of objective methods at the trial demonstrate the stresseless and radioprotective effects of xenon.